Advertisement

Let's just do one and you'll see how it works:

2x + 3y = 20 and -2x + y = 4
See how these guys are the same,
 but with a different sign?

If we add the two equations -- straight down, those x critters are going to drop right out!

Just add "like terms" and drag the "=" down to:

( 2x + 3y = 20 ) + ( -2x + y = 4 ) = ( 0 + 4y = 24 ) ... 4y = 24 ... y = 6

We've got one of them...  Now, we just need to get the x.  To do this, you can stick the y into either of the original equations...

The second equation is easier:

stick the y = 6 into -2x + y = 4 for y, which gives -2x + 6 = 4 ... -2x = -2 ... x = 1

It looks like the answer is (1, 6).

Check it!  (In BOTH equations!)


TRY IT:

Solve by elimination:

7x + 4y = 2 and 9x - 4y = 30

* Notice that the y is ready to drop out!